Por uma educação Freire-CTS: problematizando o referencial curricular gaúcho - Oliveira, Daniele Javarez de (2023)
The present dissertation had as a research problem: from the implementation of the Base Nacional Comum Curricular (BNCC), the Referencial Curricular Gaúcho (RCG) dialogues with the perspective of CTS Education and what are the implications for the Teaching of Science/Physics? To help answer the problem, the specific objectives are structured as follows: to situate the context of CTS Education in Physics teaching and its relationship with the BNCC through the minutes of the main events of Physics and Science teaching; to identify whether the Reference Matrix indicates relationships with CTS education; and to understand how the Gaúcho Curricular Reference relates aspects of CTS Education to Physics Teaching. For the analysis of the results, Textual Discourse Analysis was used. In the research on the annals of the events, we reached the category: implications for an STS Education from the BNCC, in which it was possible to realize that the authors of the papers published in Physics and Science events bring aspects that indicate approximations of the BNCC with CTS Education, whether from the themes proposed by the Base or through some competencies and skills that also signal similarities in providing Scientific Literacy. It was also observed that some of the works pointed out more specific issues, for example, for there to be an effective relationship it is necessary to bring discussions from the perspective of science and technology, involving economics, politics, and society. When analyzing the Referencial Curricular Gaúcho, as well as the Reference Matrix, used as curriculum in the state schools of São Borja, the following categories emerged: Elements of CTS Education, Criticality and Scientific Knowledge; Freirean Elements: Curriculum vs. Methodology; and Curriculum delimited by contents. With these categories, it was possible to realize that the RCG enables the development of CTS Education since it mentions assumptions of it and the education suggested by Freire. However, such mentions may be distant from critical education, since, with the references adopted in this work, it is possible to realize that CTS Education goes beyond its use as a slogan, and for it to occur effectively it is also necessary to consider the use of the Thematic Approach. Moreover, it was possible to notice, in the RCG text, mentions of Freirean terms, however, this does not characterize that there are suggestions to develop a liberating education, because education will be liberating when students recognize their reality and, from the problematizing dialogue, have conditions to change it.